1994
DOI: 10.1007/bf01374548
|View full text |Cite
|
Sign up to set email alerts
|

Reactive compatibilization of ABS/Nylon 6,6 blends: Effects of reactive group concentration and blending sequence

Abstract: Styrene-acrylonitrile-glycidyl methacrylate (SAG) copolymers with various glycidyl methacrylate (GMA) contents have been used to compatibilize the incompatible blends of acrylonitrile-butadiene-styrene (ABS) and nylon 6,6 (N66) by varying the blending sequences. When the epoxy group of SAG copolymer makes contact and reacts with the amine endgroup of N66, the resultant grafted products, SAG-g-N66, tend to reside at interface and act as compatibilizers of the blends. For a SAG copolymer with lower GMA content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…On the contrary, the greater the SAG8 content in the SAN/LCP (90/10) blend, the lower the impact strength. This is because higher GMA content in SAG may produce excessively grafted copolymers, which is considered to be less effective on compatibilization 9, 12. Figure 12 shows the effect of SAG2 content, with and without catalyst, on the tensile modulus for the SAN/LCP/SAG2 (90/10/ x ) blends.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the greater the SAG8 content in the SAN/LCP (90/10) blend, the lower the impact strength. This is because higher GMA content in SAG may produce excessively grafted copolymers, which is considered to be less effective on compatibilization 9, 12. Figure 12 shows the effect of SAG2 content, with and without catalyst, on the tensile modulus for the SAN/LCP/SAG2 (90/10/ x ) blends.…”
Section: Resultsmentioning
confidence: 99%
“…However, these mechanical properties deteriorated considerably when the SMA content was above 10 wt %. In a continuous program to investigate the in situ compatibilization of polyblends, we have reported a series of reactive compatibilized blends based on GMA‐containing copolymers involving the following polymer pairs: polystyrene (PS)/poly(ethylene terephthalate) (PET),9 PS/poly(butylene terephthalate) (PBT),10 acrylonitrile–butadiene‐styrene (ABS)/phenoxy,11 ABS/nylon 6,6,12 ABS/PBT, 13 Noryl/LCP,14 and PS/LCP 15. In this study, we report SAG‐compabilized polymer blends of SAN and LCP, their miscibility, morphology, and correlation with their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Blending sequence, which signicantly inuences the kinetics of interfacial reactions in reactive compatibilization, was also applied to improve the compatibilization efficiency and manipulate the morphology of the obtained blend. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] Hale et al found that the low-temperature and roomtemperature mechanical properties of the poly(butylene terephthalate)/acrylonitrile-butadiene-styrene (PBT/ABS) blends compatibilized by methyl methacrylate-glycidyl methacrylateethyl acrylate terpolymers (MGE) correlated tightly with the blending sequence. 30 Lee et al indicated that the morphologies of the blends were determined not only by some general factors such as viscosity ratios of the components and interfacial tension between two polymers, but also by melting sequences of the components and reaction rates of the functional groups; considering these interrelated factors, an appropriate blending sequence was required to optimize the compatibilization of the immiscible blends.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the alloy made by PA66/ABS could provide broader application than that of PA6/ABS. Chang et al [26] studied properties of PA66/ABS blends by using styrene‐acrylonitrile‐glycidyl methacrylate (SAG) as a compatibilizer. But the improvement on the compatibility is limited, and at this stage no clear explanation is provided.…”
Section: Introductionmentioning
confidence: 99%